A retrospective review of fluid balance control in CRRT - Davies, H.; Leslie, Gavin; Morgan, D. (Elsevier Inc, 2016)
Introduction: An effect of severe acute kidney injury (AKI) is the development of oliguria and subsequent retention of fluid. Recent studies have reported an association between fluid overload and increased mortality in critically ill patients. Achieving fluid balance control through haemofiltration is an important part of dialysis dose delivery in continuous renal replacement therapy (CRRT). Aims: (1) Compare the prescribed dose with the delivered dose of dialysis and haemofiltration for CRRT. (2) Identify how interruptions and delays in treatment delivery impact on fluid balance management. Method: A retrospective cohort study was undertaken of daily fluid balance and fluid removal for patients who required CRRT. Each observation chart and prescription order for every treatment day was reviewed. Each patient was exposed to the same treatment mode, predilutional continuous veno-venous haemodiafiltration (CVVHDf). A comparison was made of fluid balance control delivered to the patient over 24h against the dose of fluid removal prescribed. RESULTS: The observation charts of 46 consecutive patients were reviewed for total of 288 treatment days. Median number of days patients received CRRT was 5 (range 1-31). Median circuit life was 16h (range 0-66). Fluid removal targets did not occur in 75 (26%) treatment days. Median daily fluid removal shortfall was 300mL (range 25-3800mL). Mean number of daily treatment interruptions 1.25, SD±0.49. The most frequent cause of treatment downtime was circuit clotting (45%). Mean length of treatment down time was 3.71, SD±4.36h excluding delays attributed to assessment of renal function. Conclusion: In over a quarter of treatment days prescribed fluid removal was not achieved. Frequency of interruptions and delays in resumption of treatment compromised fluid balance control. Daily targets for fluid removal which are not achieved contribute to fluid overload and may compromise the outcome of patients who require CRRT.